Social policy in Mexico and Argentina - Martha Tepepa (Levy Economics Institute of Bard College, 2019)
This paper is a comparison between two programs implemented to combat poverty in Latin America: Prospera (Prosper) in Mexico and Asignación Universal por Hijo (Universal Assignment for Child) in Argentina. The first section offers a review of the emergence of the welfare state, examining economic and urban development in both countries and the underlying trends of social policy instruments. The analysis is based on the political nature of social problems and the actions undertaken to confront them. The paper offers a theoretical perspective, often questioning the very foundation of the social policy that serves as the main framework for the social programs, in order to present the policies' scope, successes, and disadvantages with reference to social equity and the wellbeing of their participants.
Keywords: H75; I30; I38; O18; O19; O57; P52; 330; Social Policy; Welfare State; Conditional Cash Transfers; Argentina; Asignación Universal por Hijo; Plan Jefes y Jefas de Hogar Desocupados; Mexico; Prospera; Latin America